Management of Hyperglycemia in Hospitalized Patients Receiving Parenteral Nutrition - Schönenberger, Katja A.; Reber, Emilie; Dürig, Christa; Baumgartner, Annic; Efthymiou, Andriana; Huwiler, Valentina V.; Laimer, Markus; Bally, Lia; Stanga, Zeno (Frontiers in Clinical Diabetes and Healthcare, 2022)
Almost half of inpatients on parenteral nutrition experience hyperglycemia, which increases the risk of complications and mortality. The blood glucose target for hospitalized patients on parenteral nutrition is 7.8 to 10.0 mmol/L (140 to 180 mg/dL). For patients with diabetes, the same parenteral nutrition formulae as for patients without diabetes can be used, as long as blood glucose levels can be adequately controlled using insulin. Insulin can be delivered via the subcutaneous or intravenous route or, alternatively, added to parenteral nutrition admixtures. Combining parenteral with enteral and oral nutrition can improve glycemic control in patients with sufficient endogenous insulin stores. Intravenous insulin infusion is the preferred route of insulin delivery in critical care as doses can be rapidly adjusted to altered requirements. For stable patients, insulin can be added directly to the parenteral nutrition bag. If parenteral nutrition is infused continuously over 24 hours, the subcutaneous injection of a long-acting insulin combined with correctional bolus insulin may be adequate. The aim of this review is to give an overview of the management of PN-associated hyperglycemia in inpatients with diabetes.